(untitled) (REVISTA NODO, 2025)
This article delves on the use of podcasting as an alternative communication tool to highlight the participation of women in the political and cultural spheres of the Arauca department in Colombia. Through the audio production Alma llanera, voz de mujer, the study explores the potential of digital journalism to build inclusive narratives from peripheral territories, where patriarchal structures and limited female representation in mainstream media shape social and cultural dynamics. The research employed a qualitative methodology, combining documentary review and semi-structured interviews with female leaders from the municipality of Arauca. The analysis is grounded in theoretical frameworks on communication for social change, narrative journalism, and digital media, drawing on the contributions of Kovach and Rosenstiel (2012), Ruiz and Téllez (2018), and Strano (2018). The findings show that podcasting enables direct audience engagement, facilitates the recovery of oral memory, and promotes storytelling that challenges gender stereotypes. It is concluded that digital journalism, through formats such as podcasts, is an effective strategy to strengthen the visibility and leadership of women in the sociocultural transformation of their territories, contributing to the redefinition of urban and rural spaces from a gender perspective.